Filosofi Dasar Pemikiran Ekonomi Syariah: Antara Nilai Spiritual Dan Prinsip Keadilan - Aini, Fauqah Nuri; M, Mawardi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islamic economics is an economic system based on Islamic principles, integrating spiritual values and ethics into economic activities. This paper aims to examine the fundamental philosophy of Islamic economic thought, focusing on the relationship between spiritual values and principles of justice in Islamic economics. In Islamic economic thought, prosperity is not only viewed as the achievement of material gain, but also as an effort to realize social justice, balance, and sustainable prosperity. The spiritual values in Islamic economics emphasize sincere intentions (ikhlas) in every transaction, while the principle of justice is applied through the prohibition of usury (riba), uncertainty (gharar), and speculation (maysir), as well as the implementation of wealth redistribution through zakat, waqf, and infak. Moreover, Islamic economics also emphasizes the importance of social responsibility and solidarity among individuals to create a just and prosperous society. By integrating moral and spiritual aspects in economic management, Islamic economics offers an alternative economic system that is more inclusive, ethical, and sustainable, providing solutions to the challenges faced by the global conventional economic system.